PENENENTUAN HARGA POKOK PRODUKSI BERDASARKAN METODE HARGA POKOK PESANAN PADA PENJAHIT MELYZZA KIJANG - Meidi Yanto, (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to determine the cost of goods manufactured determination which has been done by Melyzza Kijang tailors and based on the cost of order method with the full costing approach. The results of this study indicate that there is a difference in the calculation of the cost of the order made by the company compared to the cost of the order using the full costing method, which is Rp. 6,132.00 and there is a profit difference of Rp. 2,452,800.00 or 3.1%. The conclusion of this study is that using the cost of order by using the full costing method will make the cost of goods higher due to the addition of depreciation costs that have never been calculated by the company.